2022
DOI: 10.1086/721148
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Lansing Effect: Maternal Age and Provisioning Affecting Daughters’ Longevity and Male Offspring Production

Abstract: Maternal age effects on life history of offspring has been demonstrated in a variety of organisms, more often than not offspring of older mothers having lower life expectancy (Lansing effect). However, there is no consensus on how general this phenomenon is and what are the genetic and epigenetic mechanisms behind it. We tested the predictions of Lansing effect in several Daphnia magna clones in and observed a significant genotype-by-maternal age interaction, indicating clone-specific magnitude and direction o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 82 publications
(67 reference statements)
1
13
0
Order By: Relevance
“…Thus, the authors concluded that increased early life reproduction traded-off with lifespan and that maternal age effects were a result of better offspring provisioning by older mothers. Similarly, Anderson and colleagues [20] studied multiple strains of Daphnia magna and found an “inverse Lansing Effect” in some strains, in which offspring of older mothers lived longer than offspring of younger mothers. They hypothesized that this inverse effect could be a result of decreased lipid offspring provisioning by older mothers, which could result in embryonic caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the authors concluded that increased early life reproduction traded-off with lifespan and that maternal age effects were a result of better offspring provisioning by older mothers. Similarly, Anderson and colleagues [20] studied multiple strains of Daphnia magna and found an “inverse Lansing Effect” in some strains, in which offspring of older mothers lived longer than offspring of younger mothers. They hypothesized that this inverse effect could be a result of decreased lipid offspring provisioning by older mothers, which could result in embryonic caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
“…In Daphnia pulex , advanced maternal age decreased offspring lifespan in two of three clones studied, but advanced maternal age led to higher growth rates in offspring in all three clones [19]. In Daphnia magna , five clones showed positive, negative, and neutral maternal age effects on lifespan [20]. Such high intraspecific variability in maternal age effects within these model arthropods and rotifers demonstrates the importance of including multiple strains or populations in future studies of maternal age effects in other clades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study we focus on the regularly occurring cases of late-life restoration of reproductive function in Daphnia - a freshwater planktonic crustacean that is a classic model organism in aging and longevity research (Ingle 1933), which is enjoying a revival due to contemporary genomic tools (Miner et al 2012), generating a significant new data on aging (Schumpert et al 2015; Constantinou et al 2019; Cai et al 2020; Hearn et a; 2021; Nguyen et al 2021; Anderson et al 2022; Cho et al 2022). Daphnia are particularly suitable for cohort longevity and reproductive senescence studies because their reproduction mode, the cyclic parthenogenesis, allows to create cohorts of genetically identical and yet fully outbred individuals, thus providing an advantage over the use of inbred lined customary in Drosophila or C. elegans longevity studies.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies on aging hallmarks in Daphnia indicate that mitochondrial dysfunction is an unlikely cause of aging (and therefore its reversal an unlikely cause of reproductive rejuvenation), as little if any reduction of respiratory activity of mitochondrial membrane potential occurs at old age (Anderson et al 2022). On the other hand, accumulation of oxidized lipids and misfolded proteins in the forms of lipofucsins and amyloids has been shown to increase with age (Lowman & Yampolsky 2023).…”
Section: Introductionmentioning
confidence: 99%